Dissimilatory Fe(III) Reduction Controls on Arsenic Mobilization: A Combined Biogeochemical and NanoSIMS Imaging Approach - Lopez-Adams, Rebeca; Newsome, Laura; Moore, Katie L.; Lyon, Ian C.; Lloyd, Jonathan R. (Frontiers in Microbiology, 2021)
Microbial metabolism plays a key role in controlling the fate of toxic groundwater contaminants such as arsenic. Dissimilatory metal reduction catalysed by subsurface bacteria can facilitate the mobilisation of arsenic via the reductive dissolution of As(V)-bearing Fe(III) mineral assemblages. The mobility of liberated As(V) can then be amplified via reduction to the more soluble As(III) by As(V)-respiring bacteria. This investigation focused on the reductive dissolution of As(V) sorbed onto Fe(III)-(oxyhydr)oxide by model Fe(III)- and As(V)-reducing bacteria, to elucidate the mechanisms underpinning these processes at the single cell-scale. Axenic cultures of Shewanella sp. ANA-3 wild-type cells (able to respire both Fe(III) and As(V)) were grown using 13C-labelled lactate on an arsenical Fe(III)-(oxyhydr)oxide thin film, and after colonisation, the distribution of Fe and As in the solid phase was assessed using nanoscale secondary ion mass spectrometry (NanoSIMS), complemented with aqueous geochemistry analyses. Parallel experiments were conducted using an arrA mutant, able to respire Fe(III) but not As(V). NanoSIMS imaging showed that most metabolically active cells were not in direct contact with the Fe(III) mineral. Flavins were released by both strains, suggesting that these cell-secreted electron shuttles mediated extracellular Fe(III)-(oxyhydr)oxide reduction, but did not facilitate extracellular As(V) reduction, demonstrated by the presence of flavins yet lack of As(III) in the supernatants of the arrA deletion mutant strain. 3D reconstructions of NanoSIMS depth-profiled single cells revealed that As and Fe were associated with the cell surface in the wild-type cells, whereas for the arrA mutant only Fe was associated with the biomass. These data were consistent with Shewanella sp. ANA-3 respiring As(V) in a multistep process; first the reductive dissolution of the Fe(III) mineral released As(V), and once in solution, As(V) was respired by the cells to As(III). As well as highlighting Fe(III) reduction as the primary release mechanism for arsenic, our data also identified unexpected cellular As(III) retention mechanisms that require further investigation.